Civil Cases Proof Peculiarities of Road Traffic Accidents Damages - D. N. Polyakov (Сибирское юридическое обозрение, 2012)
The author reveals proof peculiarities in civil cases of reparation of damages harmed by road traffic accident, in relation to the determination of a respondent (debtor). In the article are analyzed the appropriate norms of the RF Civil code regulating the rules and conditions of civil liability for damage caused by using a transport facility as a source of danger.